Magmatic to hydrothermal conditions in the transition from the A-type Pikes Peak granite (Colorado) to its related pegmatite - Fonseca Teixeira, Ludmila Maria; Troch, Juliana; Allaz, Julien; Bachmann, Olivier (Frontiers in Earth Science, 2022)
Fluid exsolution in magmas is a process that, in many silicic upper crustal reservoirs, starts at relatively low crystallinities (near liquidus), and precedes the precipitation of many ore bodies, including pegmatites. As any magmatic system approaches its solidus, the amount of the exsolved fluid phase increases and becomes progressively dominant over melt, allowing local over pressurization and the generation of pegmatitic pods/dykes. Such pegmatitic bodies show several features that point to both magmatic and hydrothermal environments, linking those realms and providing a unique opportunity to document and understand the magmatic-hydrothermal transition within silicic magmatic systems. We studied the 1.1 Ga classic A-type Pikes Peak granite (Colorado, United States) and one of its many internally-hosted pegmatites, the Wellington Lake pegmatite, to investigate the changes that occur within a granitic system as it crosses its theoretical water-saturated solidus and continues crystallizing beyond it. Textural and geochemical analyses of quartz, plagioclase, and K-feldspar minerals, as well as fluid inclusion studies, demonstrate this magmatic to hydrothermal transition in the granite and the pegmatite. Different thermometers (Ti-in-quartz, 2-feldspars, fluid inclusions) document the temperature evolution of the granitic system, from >850°C for the hottest magmatic minerals to <400°C for the pegmatite core. The magmatic-hydrothermal transition is recorded by plagioclase and quartz rims that yield temperatures well below the traditionally inferred haplogranite solidus. In the pegmatite, the magmatic-hydrothermal transition is observed between the graphic granite wall zone, which shows homogeneous quartz geochemical signatures at near-solidus conditions (700–670°C), and the intermediate zone, which crystallized at much colder temperatures (470–420°C). Although a significant process, our calculations suggest that subsolidus precipitation from exsolved, solute-rich magmatic fluids represent less than 20% of the total volume of the granite.